Filter Rules Based on Price and Volume in Individual Security Overreaction - Cooper, Michael (Review of Financial Studies, 1999)
Journal Article Filter Rules Based on Price and Volume in Individual Security Overreaction Get access Michael Cooper Michael Cooper Krannert School of Management Address correspondence to Michael Cooper, Krannert School of Management, 1310 Krannert Building, West Lafayette, IN 47907, or email: mcooper@mgmt.purdue.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 12, Issue 4, 2 July 1999, Pages 901–935, https://doi.org/10.1093/rfs/12.4.901 Published: 01 June 2015